Efficacy of adding ramipril (VAsotop) to the combination of furosemide (Lasix) and pimobendan (VEtmedin) in dogs with mitral valve degeneration: The VALVE trial. (18th September 2020) - Wess, Gerhard; Kresken, Jan‐Gerd; Wendt, Ralph; Gaugele, Juliane; Killich, Markus; Keller, Lisa; Simak, Julia; Holler, Peter; Bauer, Alexander; Küchenhof, Helmut; Glaus, Tony
Abstract: Background: Triple therapy (TT) consisting of furosemide, pimobendan, and an angiotensin‐converting enzyme inhibitor (ACEI) frequently is recommended for the treatment of congestive heart failure (CHF) attributable to myxomatous mitral valve disease (MMVD). However, the effect of adding an ACEI to the combination of pimobendan and furosemide (dual therapy [DT]) so far has not been evaluated prospectively. Hypothesis: Triple therapy will extend survival time compared to DT in dogs with CHF secondary to MMVD. Animals: Client‐owned dogs presented with the first episode of CHF caused by MMVD. Methods: Prospective, single‐blinded, randomized multicenter study. One‐hundred and fifty‐eight dogs were recruited and prospectively randomized to receive either DT (furosemide and pimobendan) or TT (furosemide, pimobendan, and ramipril). The primary endpoint was a composite of cardiac death, euthanasia for heart failure, or treatment failure. Results: Seventy‐seven dogs were randomized to receive DT and 79 to receive TT. Two dogs were excluded from analysis. The primary endpoint was reached by 136 dogs (87%; 66 dogs, DT; 70 dogs, TT). Median time to reach the primary endpoint for all dogs in the study was 214 days (95% confidence interval [CI], 168‐259 days). Median time to reach the primary endpoint was not significantly different between the DT group (227 days; interquartile range [IQR], 103‐636 days) compared with TT group (186 days; IQR, 72‐453 days; P = .42). Conclusions and Clinical Importance: Addition of the ACEI ramipril to pimobendan and furosemide did not have any beneficial effect on survival time in dogs with CHF secondary to MMVD.